기본간호학 실습 교수법의 활용 실태와 교수자의 경험 탐색: 혼합 연구. - 최동원; 김경미; 박민정; 최한교; 송영신; 이주희 (Journal of Fundamental Nursing Science, 2026)
Purpose: This study examined the use of teaching methods in the fundamental nursing practicum and explored faculty experiences using a mixed-method design. Methods: A nationwide survey of 78 faculty members and in-depth interviews with 7 participants were analyzed using descriptive statistics and Colaizzi’s qualitative method. Results: The quantitative findings showed that team-based learning (48.7%) and flipped learning (47.4%) were the most frequently used methods and were also rated as the most effective methods (29.5% each). Faculty members identified lack of time (64.1%) and financial constraints (47.4%) as the major barriers to adopting teaching methods and selected practicum environment quality (33.3%) and instructor expertise (29.5%) as the most important factors for improving quality. The qualitative findings yielded four theme clusters: professional practices for enhancing nursing competence, constraints on practicum under limited resources, uncertainty in applying new teaching methods, and the gap between education and clinical practice. Conclusion: This study examined the use of teaching methods and faculty experiences in the fundamental nursing practicum through a mixed-method design and identified factors that contribute to or restrict the quality of practicum education. These findings can serve as an evidence-based basis for the effective design and operation of the fundamental nursing practicum. Future studies are needed to clarify policy support for improving the practicum environment and strengthening instructor expertise.